AN INTENSE SURVEY OF WEATHER FORECASTING BASED ON MACHINE LEARNING AND DEEP NEURAL NETWORK - Awadhiya, Deepika; Chandrakar, Omprakash; Shameem, Bakhtawer (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The weather forecast determines the future state of the weather. Weather forecasting is very important because both agriculture and business sector rely on weather forecasts. We use artificial neural network and data mining technique to predict weather conditions. Weather is a dynamic process, on-liner artificial neural network (ANN) can operate as process. Our research also pointed out that deep neural network is best methods as compared to traditional algorithms. Main focus is ANN or back propagation methods. Back propagation method is best approach for variation of data as well as long- range weather forecasting. This system will take the parameter and predict weather after analyzing the input information with the information in database. Consequently, two basic functions to be specific classification (training) and prediction (testing) will be performed. The outcomes demonstrated that these data mining procedures can be sufficient for weather forecasting.